THE IMPACT OF CSR ON SHAREHOLDER VALUE - Salgar, Arunkumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The impact of Corporate Social Responsibility (CSR) initiatives on shareholder value is examined in this paper, along with the ways in which socially conscious business practices affect market perceptions and firm performance. Based on a thorough analysis of the body of research and empirical data, the study explores whether and how CSR investments can improve risk management, competitive differentiation, and financial results. The research shows that CSR initiatives, from community involvement to ethical labor practices and environmental sustainability, can boost investor confidence and result in long-term value creation by examining case studies and statistical data from a variety of industries. According to the findings, although the direct financial benefits of corporate social responsibility (CSR) may differ depending on the industry, enhanced market valuation and stakeholder trust are typically associated with the strategic integration of CSR into core business operations. By outlining the circumstances in which corporate social responsibility (CSR) investments are most likely to result in quantifiable benefits for shareholders, this paper adds to the ongoing discussion and offers guidance to investors, policymakers, and corporate executives who are interested in the long-term viability of businesses.